Research on the Abilities of the Social Networking Sites in Emergency Management - Velev, Dimiter (Research Papers, 2012)
The aim of the paper is to investigate and analyze the abilities of social networking sites in emergency management, and more particularly the processes connected with the emergence, progress and coping with the consequences due to natural disasters.The essence of emergency situations, their types and characteristics are presented in the paper.The potential natural disasters in Bulgaria are summarized.The nature of social computing and social media are comprehensively represented as integral components of the Web 2.0 technologies, that serve as a basis of the implementation of social networking sites.The characteristics and operation of the social networking sites are presented in detail. The emphasis is on their application in emergency management. The format, way of sharing, storage and processing of data is discussed, as well as the useful information retrieval from the data. Recommendations are proposed for the organizations, engaged with coping with consequences due to emergency situations and the provision of preventive preparedness to fight them.